Lessons learned from developing a patient engagement panel: an OCHIN report - Arkind, Jill (J Am Board Fam Med, 2015)
There is renewed interest in patient engagement in clinical and research settings, creating a need for documenting and publishing lessons learned from efforts to meaningfully engage patients. This paper describes early lessons learned from the development of OCHIN's Patient Engagement Panel (PEP). OCHIN supports a national network of more than 300 community health centers (CHCs) and other primary care settings that serve over 1.5 million patients annually across nearly 20 states. The PEP was conceived in 2009 to harness the CHC tradition of patient engagement in this new era of patient-centered outcomes research and ensure that patients were engaged throughout the lifecycle of our research projects, from inception to dissemination. Developed by clinicians and researchers within our practiced-based research network (PBRN), recruitment of patients to serve as PEP members began in early 2012. The PEP currently has a membership of 17 patients from 3 states. Over the past 24 months, the PEP has been involved with 12 projects. We describe developing the PEP and challenges and lessons learned (e.g., recruitment, funding model, creating value for patient partners, compensation). These lessons learned are relevant not only for research, but also for patient engagement in quality improvement efforts and other clinical initiatives.